Measuring the healthcare spatial deprivation in multiple perspectives: a case study of Ningbo city - Qian, Yue; Qiao, Guanmin; Li, Tonglu; Ma, Renfeng (Frontiers in Sustainable Cities, 2023)
Background: Equalization of medical services is fundamental to the development of people-centered urbanization in Chinese-style modernization. Under rapid urbanization, large-scale population floating has led to a mismatch between supply and demand for healthcare services and raised the tension between spatial demographic reorganization and the relative stability of public healthcare service facilities. The current studies of healthcare spatial deprivation (HSD) mainly are focus on either supply, or demand, or accessibility based on census data. Therefore, it is necessary to build a multiple index that could give a physical result by using ordinary indices and mixing them together by relative methods to overcome this problem. Measure: We chose Ningbo city, Zhejiang province, located in the eastern coastal region of China, as the study area. From 2000 to 2020, the urbanization rate rapidly increased from 55.75% to 78.0%, shown the HSD in a rapidly urbanizing city, we first consider the subdistrict as the scale, innovatively absolve the medical accessibility to the IRD , and construct the Index of Healthcare Relative Spatial Deprivation (IHRSD) framework. Based on the seventh national census data, we apply an IHRSD with EWM, 2SFCA and GDM to measure where and who are vulnerable to deprive in healthcare. Result: Measured by IHRSD, 1) There is stronger HSD in peri-urban and developed-town in Ningbo; 2) Young childhood and fertile-women are vulnerable to HSD, in fact, they are spatially deprived in healthcare; 3) The socio-demographic attribute is a significant factor in HSD, especially the level of aging and population clustering; and 4) The relationship between HSD and accessibility shows an inverted U-shaped structure. Conclusion: Our experiments show that the problems of HSD are mainly from the characteristics of the population, the layout of healthcare service institutions, the accessibility of the traffic system and the natural conditions. Although the constructions of equalization of primary medical and health services, hierarchical diagnosis and treatment, and the "healthcare complex" are currently trying to reduce the phenomenon of HSD. Faced with groups and location, the acquisition of the accurately healthcare service supply is the key to realizing healthcare spatial equity.